How the Word Adjacency Network (WAN) works. (8th October 2021) - Brown, Paul; Eisen, Mark; Segarra, Santiago; Ribeiro, Alejandro; Egan, Gabriel
Abstract: The Word Adjacency Network (WAN) method is a newly invented method for attributing the authorship of texts based on internal evidence about the proximities of high-frequency words in those texts. The method has been the subject of mathematically rigorous explanations in scientific journals and here is offered instead a relatively non-technical account for humanist readers unfamiliar with advanced mathematical nomenclature. The description will refer to the operation of the algorithm as it is implemented in a newly completed open-source, open-access version that the authors have made available for free unlimited download on the WorldWide Web.